2013
DOI: 10.1111/imm.12037
|View full text |Cite
|
Sign up to set email alerts
|

Local expression of interleukin‐2 by B16 melanoma cells results in decreased tumour growth and long‐term tumour dormancy

Abstract: SummaryThe tumour microenvironment is complex containing not only neoplastic cells but also a variety of host cells. The heterogeneous infiltrating immune cells include subsets of cells with opposing functions, whose activities are mediated either directly or through the cytokines they produce. Systemic delivery of cytokines such as interleukin-2 ( IL-2) has been used clinically to enhance anti-tumour responses, but these molecules are generally thought to have evolved to act locally in a paracrine fashion. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…Additionally, Gerber et al . 56 have shown that a higher Il-2 level in the tumour microenvironment enhances the number of IFN-γ-producing CD8+ T-cells, which attenuate B16 melanoma growth and stimulate cellular dormancy. Although our results do not directly demonstrate the dependence of MeSC quiescence on CD8+ T-cells, they are consistent with this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Gerber et al . 56 have shown that a higher Il-2 level in the tumour microenvironment enhances the number of IFN-γ-producing CD8+ T-cells, which attenuate B16 melanoma growth and stimulate cellular dormancy. Although our results do not directly demonstrate the dependence of MeSC quiescence on CD8+ T-cells, they are consistent with this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was isolated and qRT-PCR was performed as described previously [20]. The intron-spanning forward and reverse primers used were designed in-house and obtained from Eurofins MWG Operon.…”
Section: Methodsmentioning
confidence: 99%
“…Now IL-2 has some clinical application in cancer therapy such as: as specific cellular anti-tumor immunity and cytokine induced killer (CIK) cells in cancer therapy. [18][19][20] Early documented research results in data bank have indicated that clinical significance of IL-2 to boost and maintain the balance of both innate and adaptive cellular immunity and even now IL-2 continues to be a key solution for most of melanoma and renal cancer. [21][22][23] In our current research we have proven that IL-2s affects on phenotypes and functions of BMDCs were present.…”
Section: Discussionmentioning
confidence: 99%